The Effect of Collateral, Debtor Character, Business Conditions and Managerial Ability on Non-Performing Loans At PT BPR Duta Paramarta - Gultom, Hamonangan J.; Sebayang, Erna S.; Manurung, Melda Br (Lembaga Jurnal & Seminar Universitas Pembangunan Panca Budi, 2024)
This study aims to examine the influence of collateral, debtor character, business conditions, and managerial ability on non-performing loans at PT. BPR Duta Paramarta. The research methodology employed is quantitative research with a descriptive approach. Data collection techniques utilized in this study involve survey methods with questionnaire instruments. The population in this research comprises all debtors of PT. BPR Duta Paramarta, with a sample size of 30 debtors. Data analysis consists of data quality tests, classic assumption tests, and hypothesis testing (T-test and F-test). The results of this study indicate that: 1) Collateral has a significant negative effect on non-performing loans, 2) Debtor character has a negative but insignificant effect on bad credit, 3) Business conditions have a significant negative effect on managerial performance, and 4) Managerial ability has a significant negative effect on non-performing loans.